The main of light poems - Cayanan, Mark Anthony R. (2007)
"The main of light" is a collection of 46 poems, 20 of which have been written specifically to form a lyric sequence. The introduction, "Eyeing the 'I'," aims to articulate the issues that inform the writing of these poems. In particular, the introduction aims to provide: a personal history of how I started in the writing of poetry; a haphazard examination of the literary tradition I am drawn to and that has shaped me; a tribute to Michelle Pfeiffer and Greta Garbo, whose faces and celebrity serve as personal and literary tropes; all of which contribute to an appraisal of my poetry, the overriding concern of which is the performance of the self. An examination of my personal history would reveal the impetus for my poetry: as a gay child, I was already aware of the profound discordance between the body I was born with and the body I wished to occupy. In other words, I wanted to be someone else. Or anyone else, for that matter, just as long as that ideal was a woman. The earliest manifestation of this was my fetishistic attachment to certain parts of figures culled from mythology and religion. Later on, I found myself drawn to an originary influence: a beautiful classmate from elementary who wrote poetry. But I felt in my desire for union with her (not actually to coalesce with but to displace) the impossibility of fulfillment. Thus, the writing of poetry for me became a means to perform, be as close as possible to, a role. This attachment to female figures, this need for identification was what initially attracted me to confessional poetry, a mode of verse that intensely scrutinizes private distress. The distress was alluring to me, primarily because of the glamour it implied: the suffering of Anne Sexton and Sylvia Plath, rendered in all its rawness in their poems, conveyed to me how possibly expansive, how grand their lives were. And because of my fixation with women compels me to be derivative, I started to write poetry that consciously followed their mold. This poetic tradition, however, has become subject to disparaging evaluations. It has been said that confessionalism is an exhausted mode, the stance of the poet as either exhibitionist or victim adopted by so many writers to the point of saturation. Confessionalism has also been said to encourage self-absorption among its practitioners: the confessional poet is the one who confesses in order to circuitously elicit admiration. Most importantly, confessional poetry has been considered a triumph of the content over the form; this mode of writing, in other words, lacks imagination and formal dexterity. While these points seem valid--they, in fact, are evaluations I quite believe in--a review of confessional poetry may reveal their vulnerability. In particular, the charge regarding confessional poetry's lack of formal sophistication is questioned in light of the works of Plath and John Berryman, two of the mode's figureheads. For instance, the "tricks" Plath displays in "Daddy" reveal her adherence to a poetics that employs the more complex turns of modernism and presages postmodern aesthetics. Berryman, too, displays the sort of formal dexterity that actually seems quite contemporary in its flavor. His fracturing of the single persona in The Dream Songs lends to the reader a certain freedom, a manner of reading encouraged for the postmodern fragment. There is much to love about the fragment in confessional poetry, in the way that it presents a paradox between the persona that wishes to be known to the reader and the persona that does not allow for fixed determination. The result, the truth that cleaves to these two--in my mind, at least--is amplification: refusal has its own magnetic pull, something that is apparent in the case of both Michelle Pfeiffer and Greta Garbo. Consider the merciless architecture of their faces: they elicit not compassion or congeniality, but awe. Consider their best-received performances, which seem to draw from the aloofness of their projections. Consider the skittishness of both women during interviews, which indicate a desire to transmogrify their celebrity--and the scrutiny of their private lives that the status seems to demand--into ellipses rather than exclamation points. These two icons may make for ideal tropes for my poetry. The poems in the thesis collection, possibly more that anything, constantly privilege the "I." The "I" in my poems seems to most resemble the confessional "I", which exhibits a seemingly different trajectory compared to the lyric "I": while the lyric aims at expansiveness, the confessional poem establishes an "I" that, in the end, establishes itself. However, my poems are a bit more interested not in creating an "artifice of honesty"--something apparent in the confessional poems of the traditionally mimetic variety--but in creating a field where self-fashioning becomes blatant, where performance trumps reality. In the lyric sequence "The Main of Light," for instance, the persona persistently assumes several female masks, and the artificial nature of the re-embodiments is highlighted through the use of simile. This artificiality is noticeable in the performances of Garbo, who never quite managed to become the characters she was given. In acting, the possible flaw in this configuration is that the maintenance of the personality that takes on the role means that the role is poorly played. This discrepancy, however, can be perceived as a tactic for the performer to achieve self-aggrandizement, something my poetry is invested in. The introduction, however, contains more than these basic points. Its digressive turns, its gestures that indicate the ambivalence that stems from anxiety are nearly as urgent for me as its "real" content.
Eyeing the "I" : introduction -- The origin of power -- After Hansel and Gretel -- The things itself -- As employee : days in a half-life -- Glamor -- The loss -- Natural calamity : three versions of the same lacuna -- Post-op -- Gradations of sea -- Interim fugue -- About the author -- Ether -- The dream of -- The origin of power -- Young: -- Singular -- Turn of fools -- The maintenance of power -- The problem with us -- Sagada/Displacements -- The persistence of symbols -- Libido paid me a visit -- Considering the slope -- First love -- The poem of the muse -- The need for ending -- The main of light -- As mirror as body -- As Adam -- As Emma Cayanan -- The private life -- As Dina Bonnevie -- Dear tormentor, -- Coming of age -- Dear tormentor, -- Body with another -- The unmasking -- As Anne Secton -- As Penelope -- Body as air -- Method acting -- As Snooky Serna -- As Greta Garbo -- Prayer -- As -- What happens next.
"May 2007".
Thesis (M.A. English Studies : Creative Writing)--University of the Philippines Diliman.
Keywords: Philippine poetry (English).; Women in literature